Evaluasi Total Solid Susu Segar Peternak Tawang Argo Berdasarkan Standard Nasional Indonesia - Firmansyah Tri Saputra (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2018)
The purpose of this studi is to know whether Milk Total Solid (TS) from Tawang Argo Farmer has already met with Indonesian National Standard (SNI) or not. Material used is local farmer milk. Variables gathered were Fat and Milk Density then calculated using Fleischman equation to get TS value. TS from Respondent compared with SNI using paired t-test in SPSS 16. Meanwhile, Milk Density and Fat is analized descriptively in order to know how TS value formed. Investigation result shows that there is a very significant difference (P<0.01) between TS from Tawang Argo Farmer with SNI which shows berada 0.92757±0.37647 % higher. The bighest contribution of TS come from fat with 148±26% above standard, while Milk Density contribute negatively as much as -0.0035±0.0008%. In conclusion, TS milk from Tawang Argo Farmer met SNI.